CORRELATION BETWEEN LIVER FUNCTION TESTS AND FATTY LIVER DISEASE/NON-ALCOHOLIC STEATOHEPATITIS - Khan, Jibran Umar Ayub; Fayaz, Humera; Qaisar, Ayesha; Amin, Said; Shah, Azhar Zahir (Khyber Journal of Medical Sciences, 2022)
Objective: This study aims to determine the correlation between liver Function Tests and fatty liver disease/non-alcoholic steatohepatitis Methodology: This cross-sectional study was performed in two major tertiary care hospitals (Maqsood Medical complex and Hayatabad Medical Complex) in Peshawar, Pakistan, from 1st January to 30th June 2022. to The study was approved by the institutional review board of Khyber Girls Medical College/Hayatabad Medical Complex, Peshawar, Pakistan. After informed consent, all patients aged 18 years and above were included in the study. Ultrasound was performed for each patient to determine the stage of fatty liver disease. History alcoholism was ascertained in all patients. In addition, hepatitis-B surface antigen and Anti-HCV, Anti-Hepatitis E and anti-Hepatitis A were performed in all patients. A sample size of 69 patients is calculated with a 90% confidence level, 7.1% margin of error and by taking an expected percentage of non-alcoholic fatty liver disease in Pakistan as 15%. Data entry and analysis were done with SPSS version 25. Study variables were age, gender, height, weight, ALT, SGOT, and bilirubin. Results: A total of 69 patients fulfilled the inclusion criteria, with predominant female patients at 75.36%. The mean age of participants was 39.71±14.8. The mean ALT was 77.88±70.52 in the male group and 53.40±29.12 in the female group. The alkaline phosphatase was 243.29±65.27 in the male in comparison to the female group 249.36±115.07. The ALT was positively correlated with ALP (r=0.328, p-value=0.006) and bilirubin (r=0.363, p-value=0.002). However moderate positive correlation was observed between ALP and bilirubin (r=0.549, p-value=0.000).